Synthesis, characterization and corrosion inhibition property of nickel(II) and copper(II) complexes with some acylhydrazine Schiff bases - Mishra M.; Tiwari K.; Mourya P.; Singh M.M.; Singh V.P. (My University, 2025)
Ni(II) and Cu(II) complexes with 2-amino-benzoic acid (1-phenyl-propylidene)-hydrazide (Habh) and 2-hydroxy-benzoic acid (1-phenyl-propylidene)-hydrazide (Hhbh) have been synthesized and characterized by different physico-chemical and spectroscopic techniques (UV-Vis, IR & NMR). The molecular structures of the ligands and their complexes [Ni(abh)2(DMSO)2], [Ni(hbh)2(DMSO)2] and [Cu(abh)2] have also been determined by single crystal X-ray diffraction technique. In all the complexes, each ligand coordinates to metal through azomethine-N and carbonylate-O resulting a 4-coordinate distorted square planar geometry for Cu(II) complexes and 6-coordinate distorted octahedral geometry for Ni(II) complexes in which two DMSO molecules occupy the axial positions. The structure of [Cu(hbh)2] complex has been satisfactorily modeled by density functional theory (DFT) and time dependent-DFT (TD-DFT) calculations. The corrosion inhibition study of the synthesized compounds has also been performed for mild steel in 0.5 M H2SO4 medium. The activity is found in the order: Ni(II) complexes > ligands > Cu(II) complexes. The DFT study on ligands also supports the experimental observation that Habh is better corrosion inhibitor than Hhbh. © 2015 Elsevier Ltd. All rights reserved.